Branding in Higher Education - Laura Raluca Ştefan (Journal of Emerging Trends in Marketing and Management, 2020)
This study generates a new perspective on the subject of branding in higher education and it is based on a large number of research studies from different countries on several continents. The aim of the study is to look at the Romanian university’s image as the outcome of their branding efforts, and to assess differentiation and positioning strategies deployed by high education institutions in our country. The study focuses on the most important components of universities’ brands, logos and straplines (tagline), welcome addresses and how they present their own academic performance. We have taken a sample of Romanian universities and looked at the colours of their logos and the content and style of their straplines or welcome addresses. Based on Searle’s Speech Act Theory (1969, 1979), three types of speech acts have been identified in the context of Romanian higher education branding: assertives, directives and commissives. We have analysed some other components of the university brand, which were identified in previous studies: the social identity of the university, the placement of the educational institution, the employability of its graduates and its general climate. Reputation, extracurricular activities, sports and social facilities, learning environment, courses offered and community links were also assumed to represent important factors of a university's brand. Higher education institutions can obtain responses to questions of how they should represent their image in the public perception and how they can build a strong brand. We have found that Romanian universities have similar brands and our conclusion is that a better differentiation and positioning is required in higher education.